Initial Calculation of Prayer Time Based on Geolocation Using Spreadsheet - Taufikurrahman, Arief; Akbar, Fitriatma Maulani (University of Muhammadiyah Sumatera Utara, 2025)
The time of prayer is influenced by the position of the sun relative to the earth, which varies with the location and time of the observer. Astronomically, this is related to the position of latitude and longitude that can be obtained from the map using geolocation techniques. The sample of this study is the coordinates of large mosques in 15 regions in Indonesia on the 15th of each month throughout 2024. To facilitate the process of collecting and calculating data and avoiding errors in calculations, researchers use Spreadsheet calculation tools in the form of Microsoft Excel applications. This research uses a quantitative approach with an experimental method to test the effectiveness of using the coordinate points of large mosques in determining prayer times. The results show that there is a difference of about 11.2%, from a total of 900 calculation results, compared to the results of Bimas Kemenag Islam using midpoint data. This difference is relatively small because the value only ranges from less than 1 minute to more than 1 minute, so it can be used in determining the beginning of prayer time.